Re-reading Pistorius. How Do Hegemonic Masculinity, Celebrity Status, and Affective Atmosphere Help Us Understand Pistorius's Crime? - Nosal, Przemysław (Violence against women, 2025)
Oscar Pistorius's parole in January 2024 offers a new perspective on the South African runner. This article examines Pistorius within the context of social factors that influenced his behavior and the murder of Reeva Steenkamp. Drawing on Connell's gender order theory, Messner's triad of violence, and affective atmosphere, it reveals how Pistorius, despite his disability, embraced hegemonic masculinity and became a sports star. The case highlights professional men’s sports as a potential risk factor for violent behavior but underscores the need for contextualizing violence in sports, as predicting its occurrence is complex.